Risk and Exposure of Musculoskeletal Disorders among Dental Surgeons Working in Dhaka City (Update Dental College Journal, 2019)
Background: Musculoskeletal disorders (MSDs) are the most important occupational health problems particularly in dental professionals. Dentists are among the workers who are more often susceptible to this disorder, as because their work includes risk factors that may lead to this disorder. The study aims to determine the prevalence of MSDs among dental surgeons , also the risk and exposure of this disorder by assessing job postures and the correlation between them.Methods : This cross sectional study was conducted among purposively selected 86 dental surgeons working in eight different tertiary level public and private hospitals in Dhaka city. A structured questionnaire was used for data collection, where Nordic Musculoskeletal Questionnaire(NMQ) used which records the prevalence of MSDs in terms of musculoskeletal symptoms and to assess the risk and exposure of MSDs, Rapid Entire Body Assessment (REBA) score sheet, Quick Exposure Check (QEC) have been used respectively by 10- 15 minutes observing each study subject during different dental operating procedures. After data collection analysis of data was performed by using SPSS software (Version 22).Results : More than 63 % and 47 % of the participants reported pain and discomfort in at least one body region in the last 12 months and the last 7 days respectively. The major affected part was neck, followed by lower back, shoulders and hands / wrists. In different field of specialization among the study subjects musculoskeletal symptoms were highest in oral and maxillofacial surgeons followed by general practitioners, orthodontists, endodontists, prosthodontists. The exposure assessment (QEC) showed that a small percentage (22.1%) have acceptable exposure, where 30.2%, 47.7% had medium exposure and high exposure respectively. Whereas the risk assessment (REBA) showed that 59.3% of the participants were in medium risk group that necessitates further investigation and needs to implement change. Pearson’s correlation test indicated that there is a strong positive correlation between the current exposure and the risk (r = 0.832) and the relationship between exposure and risk of MSDs was found to be highly significant as p < 0.01. Highly significant association found between risk level according to REBA score and the exposure level according to QEC score with MSDs ( as p value < .01).Conclusion: This study concludes that high prevalence of MSDs and high risk levels as well as exposure levels according to REBA and QEC, suggest inappropriate and incorrect ergonomic postural habits existing among the dental surgeons which necessitates further investigation and attention on this issue to combat with this disorder among dental professionals.Update Dent. Coll. j: 2019; 9 (1): 3-7